Otimização de planos de manutenções de componentes de sistemas de distribuição de energia elétrica centrados em confiabilidade - Piasson, Diego [UNESP] (2014)
In this work, the scheduling of preventive maintenance tasks in components and equipment of electric power distribution systems, centered on system reliability is treated as a multiobjective nonlinear optimization, binary, dynamic and restricted problem. A pseudo-index of system unreliability and the costs of preventive maintenance programs are the conflicting objectives of the model proposed. The constraints considered in this modeling are the limits of the service continuity indicators (DIC - Individual Interruption Duration per Consumer unit and FIC - Interruption Frequency individual per Consumer unit) for each set of customers, the availability of maintenance crews and the limits for equipment maintenance. The modeling is focused on the equipment and components reliability indices. These indices are evaluated by an approach involving probabilistic fault models and inference fuzzy system. To solve the model is proposed an evolutionary algorithm NSGA-II. The proposed methodology was tested in three feeders, individually, and on a larger system composed of these three feeders, all belonging to an electricity distribution company in the state of São Paulo. The obtained results show the capacity of the methodology to allocate maintenance in sections considered priority and to converge for a frontier of Pareto with quality solutions. The results also show the great influence of the failure probability of power lines, more specifically, the set of components that support network cables such as crossarms, insulators, among others; about the reliability of the systems and, consequently, on the allocation of maintenance